Aircraft control and simulation - Stevens, Brian L.; Lewis, Frank L. ([S.l.] : Wiley-Interscience, 2003)
The updated revision of the well-respected book on analyzing aircraft performance This Second Edition of the bestselling Aircraft Control and Simulation has been expanded and updated to include the latest technological advances in the field. In addition, a new section on basic aerodynamics, aircraft configuration, and static stability makes this complex material more accessible to beginners. This comprehensive guide discusses the fundamental principles and theory of aircraft control and simulation. It also covers modeling and dynamic analysis, stability evaluation, multivariable control theory, and computer-aided design techniques. The inclusion of topics from geodesy and gravitation lays the groundwork for a discussion of the theory for suborbital aircraft now under development. Special features of this new edition include: * New and updated computer calculations using MATLAB(r) * A new section on basic aerodynamics, aircraft configurations, and static stability * Coverage of new MIMO design techniques, robustness theory, and nonlinear design Complete with examples of actual designs from the aircraft industry plus exercise problems, Aircraft Control and Simulation, Second Edition is an excellent reference for anyone involved in the design and modeling of aerospace vehicles and an outstanding text for both undergraduates and graduate students.